A Study of Performance Related Pay in Chinese Commercial Banks - Fan, Ruonan (2013)
With rapid economic development, Chinese banking industry and the HR areas are both changed enormously. Chinese banking industry has increased more than 10 times since 2003 and the numbers of banks in China have grown from four hundred to twelve hundred in the past three decades. In the best period for development, Chinese commercial banks are also facing severe competition, especially in retaining experienced employees. “Pay” now is regarded as the most crucial factor by Chinese employees to motivate their performance. According to Expectancy Theory (Vroom, 1964) and Equity Theory (Adams, 1965), monetary variables are a crucial part of motivation. And if the employees are rewarded fairly for their efforts, they are more likely to be motivated. As one of the best industries to adopt performance related pay, it is worth to study the PRP schemes adopted and their objectives to adopt such schemes. It may give some help to Chinese commercial banks to figure out the better way for them of motivating employees, because the theories of new pay has a shorter history in China then in the west. Also, this study tends to examine the effectiveness and problems in employee motivation in Chinese banking industry. The effectiveness and problems will be revealed through four parts: equity of PRP, behavior changing, the amount of reward and risk taking. Finally, some suggestions for future study will be given.